Achieving Sustainable Development Agenda of 2030: The Role of Accountants - Aggreh Meshack; Marcus Garvey Orji; Gilbert Ogechukwu Nworie; Mercy Siddy Aggreh (Britain International for Academic Research (BIAR) Publisher, 2022)
The study examined the contribution of accountants in achieving the sustainable development agenda of 2030. A perspective study of accountants in Nigeria was carried out to specifically determine the role of accountants in ensuring sustainable management of water and sanitation, sustainability of cities and human settlements, and sustainable consumption and production patterns. Cross-sectional survey research design was deployed for the study. A sample size of eighty-nine (89) chattered accountants was obtained from a population of seven hundred and seventy-two (772) professionally affiliated Accountants in Nigeria. Primary data were sourced from the questionnaires administered on the 89 sampled chattered accountants in Nigeria. Kolmogorov-Smirnov Test was used in hypotheses testing at 5% level of significance. The findings of the study revealed that: accountants play a significant role in ensuring availability and sustainable management of water and sanitation (D = 0.197, p = .002); accountants have a significant function in making cities and human settlements inclusive, safe, resilient and sustainable (D = 0.151, p = .001); there is a significant responsibility of Accountants in ensuring sustainable consumption and production patterns (D = 0.178, p = .000). Based on the finding, it was recommended that Accountants should help in reducing waste generation through prevention, reduction and recycling and reuse of waste.